SWOT (KEKEPAN) Analysis In Developing Competitive Tahfiz Classes At MI Al-Iman Magelang City - Aspiyah, Aspiyah; Islah, Islah; Giyoto, Giyoto (Jurnal Edusci, 2025)
MI Al-Iman, as a known Islamic private madrasah in Magelang City, must have a strategy to increase the characteristics and quality of the madrasah. The method used to form strategies by looking at internal and external aspects is by analyzing the Kekepan (strengths, weaknesses, opportunities, threats) that exist in the madrasah. The first stage of Kekepan analysis, by calculating the IFE (Internal Factor Evaluation) matrix and the EFE (External Factor Evaluation) matrix, obtained results of 2.73 and 3.34, respectively. In the IE (Internal and External) table, the position of MI Al-Iman is in cell I, namely growth, which means that the strategy is focused on improving service services in the field of Tahfizul Qur'an and increasing competitive access. Based on the results of the Analytical IFA and EFA methods and the Kekepan matrix, it was found that the best alternative is the SO (Strength Opportunity) strategy, which is a strategy that utilizes all strengths to make the most of the opportunity. The SO strategy formed is to increase cooperation with madrasas or Islamic boarding schools in the field of tahfiz Al-Quran and introduce special programs for tahfiz classes to the wider community through brochures.